WORKING CAPITAL LOANS WITH FIDUCIARY IN PT. RURAL BANK BANK SURYA YUDHA BANJARNEGARA - Ibnu Jodik Prakoso*, Kashadi, Suharto (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2014)
ABSTRACT Working capital loans is a facilities owned by PT. Rural Bank Bank Surya Yudha Banjarnegara. Working capital loans can be collateralized by fiduciary. Fiduciary arranged in Ordinance Number 42, 1999 year about Fiduciary.The Purpose of the research is to investigate the implementation of a working capital loan with fiduciary on the PT. Rural Bank Bank Surya Yudha Banjarnegara. As well to know how exeution fiduciary when debitor do wanprestatie.This legal research use empirical judicial approximation. This research based on research in the practice to understand symptoms legal which includes legal principles, legal norms, and legislation. This research associated with working capital loans with fiduciary on the PT. Rural Bank Bank Surya Yudha Banjarnegara.Based on research in the practice can be seen that the implementation of a working capital loans with fiduciary on the PT. Rural Bank Bank Surya Yudha Banjarnegara based on credit agreement between creditors and debitor. Fiduciary can be use a guarantee in credit agrement a working capital loans. Fiduciary can be use guarantee of principal, and additional collateral. Not all deed fiduciary registered to fiduciary registration office in KEMENKUMHAN regional office. Execution fiduciary with selling fiduciary object by deal the parties between creditors and debtior Keyword : Working capital loans, Fiduciary